The grounds and more serious forms of discrimination in Croatia - Bježančević, Sanja (Array, 2021)
Although the legislative framework for protection against discrimination in Croatia covers a considerable number of grounds and could be described as satisfactory, discrimination in society is present to a greater extent than that registered in complaints received by the Office of the Ombudswoman. Different treatment of a person or persons may involve several different legally protected grounds, resulting in a more serious form of discrimination defined under the Anti-Discrimination Act as multiple discrimination. The concept of multiple discrimination is very complex and multi-layered. Thus, the focus of this research was to conduct a survey on 761 respondents stratified by sex, education, and age. The chi-square test examined the relationship between the grounds of discrimination provided by respondents who declare themselves victims of discrimination in the area of work and working conditions, in the area of education and justice, and based on their sex, level of education, and age. The results of the research show that more than half of the respondents experienced some form of discrimination and that more than half of the respondents who declare themselves victims of discrimination experienced some of the more serious forms of discrimination.